Compendium of methods for the microbiological examination of foods - Salfinger, Yvonne (APHA Press, 2015)
The Fifth edition of the Compendium of Methods for the Microbiological Examination of Foods has now been fully updated. All chapters have been revised and new chapters have been added. This Compendium is the primary authority for food safety testing and presents a comprehensive selection of proven testing methods with an emphasis on accuracy, relevance, and reliability. The Compendium is a must-have for all food laboratories, food manufacturers, public health laboratories, and anyone performing food safety testing. More than 200 experts have reviewed and updated the 68 chapters in this new edition. New chapters include the following: Pet Food and Animal Feed, Beer and Wine, Probiotics, Cronobacter Species, and other chapters. Content covers general laboratory procedures, including laboratory quality assurance, meats and meat products, environmental monitoring procedures, sampling plans, sample collection, shipment, and preparation for analysis; microorganisms involved in processing and spoilage of foods; foods and the microorganisms involved in their safety and quality; indicator microorganisms and pathogens, microorganisms, food safety, and foodborne illness; preparation of microbiological materials (media, reagents, and stains); and other material.--Provided by publisher.